(untitled) (New York, N.Y., 2002)
This series provides the chemical physics field with a forum for critical, authoritative evaluations of advances in every area of the discipline. Volume 129 in the series continues to report recent advances with significant, up-to-date chapters by internationally recognized researchers.
Keywords: Chemistry, Physical and theoretical,Hóa học, vật lý và lý thuyết